2015
DOI: 10.1080/13504851.2015.1071463
|View full text |Cite
|
Sign up to set email alerts
|

Does speculation Granger cause return in Chinese commodity markets?

Abstract: We test the Granger causal relations between speculation and returns in Chinese commodity markets using quantile regression method. We find that speculation Granger causes returns in rebar, bean pulp and rapeseed oil markets. At lower quantiles, estimates are negative; but estimates are positive at upper quantiles. This indicates that larger speculation results in larger return volatility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Manera et al (2013) found short term speculation increases noise in the information formation process thereby positively affecting volatility. Hu and Feng (2016) identified that higher speculation leads to higher return volatility. Wellenreuther and Voelzke (2019) studied the relationship between speculation and volatility for metals and agricommodity futures in China and identified that volatility unidirectionally Granger causes speculation.…”
Section: Causal Relationship Between Speculation and Volatility In The Futures Marketmentioning
confidence: 99%
“…Manera et al (2013) found short term speculation increases noise in the information formation process thereby positively affecting volatility. Hu and Feng (2016) identified that higher speculation leads to higher return volatility. Wellenreuther and Voelzke (2019) studied the relationship between speculation and volatility for metals and agricommodity futures in China and identified that volatility unidirectionally Granger causes speculation.…”
Section: Causal Relationship Between Speculation and Volatility In The Futures Marketmentioning
confidence: 99%